Health Institutions in Iraq during the Ottoman Era - Khairallah Muhammad, Naseer (Journal of College of Education, 2022)
The health conditions in Iraq during the Ottoman Empire were bad, as the most basic elements of health conditions were lacking in it, so ponds and swamps with stagnant and polluted water spread, and insects spread diseases that killed many residents, and this was due to the failure of the Ottoman authorities to make any concrete efforts to treat this is the problem.The Ottoman era was characterized by a lack of interest in the health aspect, and the medical staff in that period was characterized by a lack of awareness, as well as their use of primitive methods in treating health problems that appeared during that period, as well as insufficient financial allocations for the health aspect, which led to the closure of a number of hospitals, especially in Rural areas, despite this, helped reduce the spread of epidemics and diseases through the measures they took, especially in times of outbreaks of epidemics and diseases, and thus reduce the size of losses among the population.